2011
DOI: 10.1126/science.1208897
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nonlinear Mesoscale Eddies on Near-Surface Oceanic Chlorophyll

Abstract: Oceanic Rossby waves have been widely invoked as a mechanism for large-scale variability of chlorophyll (CHL) observed from satellites. High-resolution satellite altimeter measurements have recently revealed that sea-surface height (SSH) features previously interpreted as linear Rossby waves are nonlinear mesoscale coherent structures (referred to here as eddies). We analyze 10 years of measurements of these SSH fields and concurrent satellite measurements of upper-ocean CHL to show that these eddies exert a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
491
5
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 546 publications
(565 citation statements)
references
References 22 publications
(45 reference statements)
26
491
5
9
Order By: Relevance
“…Mesoscale eddies, such as the Capricorn Eddy, stimulate and redistribute biological production in the ocean, thus creating attractive pelagic habitats for free-ranging, higher trophic level marine organisms (Chelton et al 2011, Godø et al 2012. Our results suggest that manta rays may exploit offshore mesoscale eddies for foraging purposes and corroborate several other studies that showed the importance of mesoscale eddies as offshore foraging grounds for a variety of marine species (e.g.…”
Section: Eddy Affinity and Offshore Foragingsupporting
confidence: 87%
“…Mesoscale eddies, such as the Capricorn Eddy, stimulate and redistribute biological production in the ocean, thus creating attractive pelagic habitats for free-ranging, higher trophic level marine organisms (Chelton et al 2011, Godø et al 2012. Our results suggest that manta rays may exploit offshore mesoscale eddies for foraging purposes and corroborate several other studies that showed the importance of mesoscale eddies as offshore foraging grounds for a variety of marine species (e.g.…”
Section: Eddy Affinity and Offshore Foragingsupporting
confidence: 87%
“…Such studies have previously been undertaken using satellite observations (e.g. Chelton et al, 2011). In a recent study by Everett et al (2012), it was shown that in one particular zone of the EAC region -that they referred to as "Eddy Avenue" -cyclonic eddies typically have elevated chlorophyll a at their core, while anti-cyclonic eddies have lower than average chlorophyll a.…”
Section: Snapshots Of Chlorophyll Amentioning
confidence: 99%
“…Subtracting from these temperature profiles climatological estimates of temperature from the World Ocean Atlas 2009 (WOA2009) and averaging in equally spaced bins, we developed a three-dimensional (3-D) view of upper ocean temperature anomaly surrounding SST fronts. Since a similar technique has been used to characterize mesoscale eddies [see, e.g., Roemmich and Gilson, 2001;Chaigneau et al, 2011;Chelton et al, 2011b;Hausmann and Czaja, 2012] and results in a socalled composite eddy, we refer to this 3-D average-and the associated SST and SSH averages-as a composite front. We generate this composite for subtropical regions in the North and South Pacific, North and South Atlantic and Indian Oceans-regions defined later in the study.…”
Section: Microwave Sstmentioning
confidence: 99%